Preventing Family Violence : A Multidisciplinary Approach - Chan, Edward Ko Ling (Book collections on Project MUSE., 2012)
Family violence, including intimate partner violence, elder abuse and child maltreatment, is a serious social problem that has been gaining public concern both in Chinese societies and around the globe over the past few decades. It is such a serious and complicated problem that any single discipline can only portray a small piece of the big picture. Family violence not only influences one's physical and mental health, but it also has profound effects on one's social functioning, welfare, and legal status. Fragmented approaches to the formulation of preventive strategies may only touch on the surface of individual disciplines, and therefore hamper their overall effectiveness. Integrated approaches that involve multiple disciplines appear to be more effective in tackling the problem, although they are sadly lacking to date. This book stems from the synergistic effort in the symposium. Almost all the speakers, as well as some professionals who newly joined in the undertaking, contributed to its chapters.